2020
DOI: 10.1109/tnse.2019.2941754
|View full text |Cite
|
Sign up to set email alerts
|

Mobi-IoST: Mobility-Aware Cloud-Fog-Edge-IoT Collaborative Framework for Time-Critical Applications

Abstract: The design of mobility-aware framework for edge/fog computing for IoT systems with back-end cloud is gaining research interest. In this paper, a mobility-driven cloud-fog-edge collaborative real-time framework, Mobi-IoST, has been proposed, which has IoT, Edge, Fog and Cloud layers and exploits the mobility dynamics of the moving agent. The IoT and edge devices are considered to be the moving agents in a 2-D space, typically over the road-network. The framework analyses the spatio-temporal mobility data (GPS l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
59
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 102 publications
(59 citation statements)
references
References 29 publications
0
59
0
Order By: Relevance
“…A different example of the clustering problem in distributed computing paradigms can be found in [20]. That work proposes a framework in a 4-layers environment (i.e., from down to top: IoT, edge, fog and cloud), which, by analyzing spatio-temporal mobility data and other contextual information, and by means of a machine learning algorithm, the location of IoT and edge devices that are on the move can be predicted.…”
Section: B Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…A different example of the clustering problem in distributed computing paradigms can be found in [20]. That work proposes a framework in a 4-layers environment (i.e., from down to top: IoT, edge, fog and cloud), which, by analyzing spatio-temporal mobility data and other contextual information, and by means of a machine learning algorithm, the location of IoT and edge devices that are on the move can be predicted.…”
Section: B Related Workmentioning
confidence: 99%
“…Focusing on the main objective of the FCC problem (i.e., reducing the average distance to management functions), in view of equation (2), it is clear that, depending on the distance to cloud (d ic ) and between edge devices (d ij ), which in turn determine the cost of cloud connections ( ) and fog connections ( ), respectively, as well as on the weights α and β, the number of clusters (which is not known in advance) will vary. To evaluate the impact of these parameters, equation (19) shows the average weighted cost of a connection from a node to cloud, , while equation (20) shows the average weighted cost of a (fog) connection between two nodes as:…”
Section: Influence Of Fog and Cloud Costsmentioning
confidence: 99%
See 1 more Smart Citation
“…A huge amount of data are available in manufacturing systems, waste management systems, etc., but the data and information should be properly collected, encoded and transmitted to the cloud application in order to be processed and to allow a real-time monitoring of equipment and systems. The major challenges are represented by: data acquisition from smart sensors, actuators and PLCs; data conversion; data security and privacy; data encoding, encryption and decryption [7][8][9][10].Software architectures of the big data processing platforms are analyzed in the literature, including solutions for job scheduling for big data applications [11], solutions which offer a flexible co-programming architecture able to support the life cycle of time-critical cloud native applications [12], mobility-driven cloud-fog-edge collaborative real-time framework solution, which has IoT, Edge, Fog and Cloud layers and which exploits the mobility dynamics of the moving agent [13].Several data encoding and encryption solutions for cloud applications are presented in the literature [14][15][16][17][18][19][20][21][22], but without including detailed case studies to present identified problems, propose solutions, and implement results.The main problem is the identification of the right solution that will ensure the data transmission and processing in a secure way, quickly, efficiently and with low costs. The proposed solution presented in Chapter 2 can be used both in smart factories and for smart city applications including automated waste collection systems.Waste management comprises prevention, collection (metal, paper, cardboard, aluminum cans plastic), removal, recycling, reuse, and safe disposal of toxic and dangerous waste.…”
mentioning
confidence: 99%
“…Software architectures of the big data processing platforms are analyzed in the literature, including solutions for job scheduling for big data applications [11], solutions which offer a flexible co-programming architecture able to support the life cycle of time-critical cloud native applications [12], mobility-driven cloud-fog-edge collaborative real-time framework solution, which has IoT, Edge, Fog and Cloud layers and which exploits the mobility dynamics of the moving agent [13].…”
mentioning
confidence: 99%